2022
DOI: 10.1177/2333794x221138437
|View full text |Cite
|
Sign up to set email alerts
|

The Differences Between RSV and no RSV Acute Bronchiolitis in Hospitalized Infants: A Cross-Sectional Study

Abstract: To identify the differences between the RSV and non-RSV bronchiolitis in hospitalized infants in a Greek tertiary pediatric unit and the possible risk factors related to severe forms of the illness. We performed a retrospective cross-sectional data analysis by reviewing medical records of patients that were hospitalized for acute bronchiolitis from 2012 to 2019. The patients with RSV bronchiolitis were found to require antibiotic treatment, IV fluids, adrenaline, and hypertonic saline inhalations more frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 20 publications
2
4
3
Order By: Relevance
“…Analysis of disease severity showed that aetiology may also be associated with prognosis and is therefore of significant value. We observed a more severe of disease course in children with RSV bronchiolitis, which is in line with previously published data (8,9,11) . Apart from the aforementioned apathy and fatigue during feeding, we observed a higher likelihood of oxygen therapy in RSV-positive children (OR = 3.8 in univariate analysis and OR = 4.4 in multivariate analysis); similarly, a higher need for oxygen supplementation in RSV bronchiolitis was reported by García et al in his study of 4.800 children under 2 years of age (8) .…”
Section: Univariate Regression Modelsupporting
confidence: 93%
See 4 more Smart Citations
“…Analysis of disease severity showed that aetiology may also be associated with prognosis and is therefore of significant value. We observed a more severe of disease course in children with RSV bronchiolitis, which is in line with previously published data (8,9,11) . Apart from the aforementioned apathy and fatigue during feeding, we observed a higher likelihood of oxygen therapy in RSV-positive children (OR = 3.8 in univariate analysis and OR = 4.4 in multivariate analysis); similarly, a higher need for oxygen supplementation in RSV bronchiolitis was reported by García et al in his study of 4.800 children under 2 years of age (8) .…”
Section: Univariate Regression Modelsupporting
confidence: 93%
“…Our study shows several important differences related to RSV as a specific aetiological factor. RSV was the predominant aetiological factor in acute bronchiolitis (88% of all AB hospitalisations in our series of patients), as might have been expected from published studies, although the percentage of RSV-caused AB is even higher than in previous reports, which found RSV in 60% (11) -62.7% (9) -66% (8) of AB hospitalisations. Furthermore, due to the observed seasonality, RSV was responsible for 86.4% (December) to 94.5-97.7% (January-March) of the hospitalised cases during the peak season of RSV incidence.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations